Our Laboratory Experience: Comparison of Capillary Electrophoresis/Immunosubtraction and Agarose Gel/Immunofixation - Pieri, Massimo; Tomassetti, Flaminia; Iodice, Caterina; Piazzolla, Rosa; Riboldi, Elena; Capogreco, Francesca; Innocenti, Adalgisa; Frassanito, Maria Loredana; Bernardini, Sergio; Calugi, Graziella (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Abstract. Monoclonal gammopathies represent a wide spectrum of related diseases. The common denominator is the presence of a monoclonal protein in the serum or urine, which can be in the form of intact immunoglobulin, immunoglobulin fragments, and/or free light chains (? and ?). We can detect these abnormalities by immunofixation electrophoresis (IFE) in which specific antibodies are overlaid after electrophoresis and the corresponding immunoglobulin. In our study, we compared gel-based and capillary-based serum protein electrophoresis methods to identify and characterize monoclonal immunoglobulins in serum samples. We analyzed 500 serum samples by Sebia Hydragel agarose gel electrophoresis (AGE)/immunofixation electrophoresis (IFE) and CAPILLARYS 2 capillary zone electrophoresis (CZE)/immunosubtraction (IS). AGE/IFE and CZE/IS had an overall agreement of 98% on serum protein electrophoresis. In our hands, AGE/IFE and CZE/IS had the same specificity for detection of monoclonal proteins; however, CZE/IS seems to be more sensitive than AGE/IFE for the detection of some critical cases. However, CZE/IS is an analytically suitable alternative to AGE/IFE, although laboratories should need to combine, for singular samples, both electrophoretic methods in their clinical routine. A combined use of AGE/IFE and CZE/IS is necessary to lead to an accurate diagnosis and clinically error-free results.